PELATIHAN PEMAKAIAN MESIN EDC MERCHANT BRI PADA MASYARAKAT PENERIMA BANTUAN SOSIAL (BANSOS) DAN BANTUAN PANGAN NON TUNAI (BPNT) TAHUN 2024 DALAM MENGGERAKKAN PEREKONOMIAN MASYARAKAT - Doni Syofiawan; Jackhon Pahala Simanjuntak; Rikson Pandapotan Tampubolon (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2024)
and business activity as Covid-19 cases are controlled. Riau Islands' economic growth is expected to be supported by an increasing investment component in line with improving net export performance on the expenditure side as well as increased growth in processing industry LU, construction LU and trade LU on the business side. Support for government spending through the distribution of social assistance will help maintain people's purchasing power and have an impact on increasing household consumption. Apart from that, in encouraging tourism development, especially attracting foreign tourist arrivals, a travel bubble between Singapore and Batam-Bintan was agreed upon by the two countries on January 24 2022. From the problems presented above, if MSMEs do not implement new initiatives or improve their ability to use technology, existing business opportunities will be taken by business actors from other regions and neighboring countries. Therefore, it is considered important for MSMEs to receive training on how to utilize technology to increase turnover and be able to compete nationally and internationally. Along with this, the number of poor people is increasing, therefore the government, in this case the Batam City Social Service, is participating in distributing social assistance to people in need by collaborating with BRI bank as HIMBARA bank. In this community service, the author tries to increase the turnover of Batam City MSME businesses by improving packaging, production and sales processes, funding and business capital, marketing and the use of BRI Merchant EDC machines.